PROSEDUR PENGUJIAN SUBSTANTIF ATAS SALDO KAS DAN SETARA KAS PT. XYZ OLEH KAP JOACHIM ADHI PITER POLTAK DAN REKAN - Min Fadhlillah (2022)
Substantive testing procedures are procedures designed to test and verify the correctness of the balances presented in the financial statements. Auditing cash and cash equivalent accounts is an important matter for a public accounting firm in auditing financial statements. Therefore, the audit process must first create an audit plan in order to achieve a good audit implementation in accordance with the auditor's professional regulations. In testing the cash and cash equivalent account balances, the author had the opportunity to audit PT. XYZ which is a client of KAP Joachim Adhi Piter Poltak and Partners who are engaged in the field. The procedure for substantive testing of cash and cash equivalent balances carried out by the Public Accounting Firm Joachim Adhi Piter Poltak and Partners includes, among others, making materiality, conducting confirmation controls, conducting vouching and , making inspection work papers. Based on the audit results show that the balance of cash and cash equivalents presented by PT. XYZ in the financial statements is correct without material misstatement and is in accordance with accounting standards.